2017
DOI: 10.1177/2394901517730729
|View full text |Cite
|
Sign up to set email alerts
|

Empirical Investigation on Food Inflation and Efficiency Issues in Indian Agri-futures Market

Abstract: In early 2007, the Government of India (GoI) banned futures trading on some essential agro-commodities such as wheat, rice, and two varieties of lentils due to rising food inflation. However, futures trading in agri-commodities such as chana (chickpea), soy oil, rubber, and potato were temporarily suspended. Professor Abhijit Sen’s committee, constituted to study the relationship between futures trading and agricultural commodities inflation, did not find sufficient evidence of inflationary impact of futures t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Unlike Granger causality test, TY modified Granger causality test does not require pre-testing cointegration. TY modified Granger causality test can be applied whether the given series have the same or different order of integration, and are cointegrated or not-cointegrated (Singh and Singh, 2017b). It is free from the potential bias linked with unit roots and cointegration tests (Toda and Yamamoto, 1995).…”
Section: Vector Error Correction Model (Vecm) and Vector Auto Regression (Var)mentioning
confidence: 99%
“…Unlike Granger causality test, TY modified Granger causality test does not require pre-testing cointegration. TY modified Granger causality test can be applied whether the given series have the same or different order of integration, and are cointegrated or not-cointegrated (Singh and Singh, 2017b). It is free from the potential bias linked with unit roots and cointegration tests (Toda and Yamamoto, 1995).…”
Section: Vector Error Correction Model (Vecm) and Vector Auto Regression (Var)mentioning
confidence: 99%
“…They concluded that the performance of private sector banks in respect of all the parameters was better than that of public sector banks in priority sector lending. 6 Syed Ibrahim (2012) 2 proved that RRB"s are sanctioning loan to more priority sector rather than non priority sector.…”
Section: Review Of Literaturementioning
confidence: 99%